A Theoretical Framework Based on Organizational Cul-ture and Personnel Values (Case Study: Bandar Imam Petrochemicals) - Sadegh Shattaly Nazhed, Rovis (2020)
Today, it is necessary to learn to manage and administer organizations based on values, which is also influenced by the culture and atmosphere of the organization. No comprehensive research has been done on organizational culture and personnel values. Therefore, the purpose of this study is to provide a theoretical framework based on the components of organizational culture and personnel values in Bandar Imam Petrochemical. This research is applied in terms of purpose and descriptive-exploratory in terms of data collection method and with the help of a questionnaire. The statistical population of this study includes all employees of Bandar-e-Imam Petrochemical with a total of 3622 people. The said value is variable between 425 and 850. Taking into account the probabilities related to the unusability of a number of completed questionnaires, a total of 620 questionnaires were randomly distributed in the desired area at different hours of the day, and finally 595 questionnaires were used as a basis for statistical analysis. (Organizational Culture Questionnaire and Personnel Values Questionnaire) was used. In this study, in order to determine the validity of the questionnaires through communication with elites (management professors) and the second-order confirmatory factor analysis model, all the proposed dimensions in this section (15 dimensions) were approved. Experts were located and the research model was approved. Cronbach's alpha coefficient was used for reliability of variables and questionnaires. To analyze the research data, factor analysis and confirmation of structural equation modeling and to fit the research model, SPSS and AMOS software were used. The results show that the research model has the necessary validity and there is a positive and significant relationship between organizational culture and personnel values in Bandar Imam Petrochemical. Finally, based on the importance and purpose, suggestions are presented.